Frequency distribution of the amide-I vibration sorted by residues in Amyloid fibrils revealed by 2D-IR measurements and simulations - Falvo, Cyril (2012)
The infrared optical response of Amyloid Fibrils Aβ(1–40) is investigated. Simulations of two models corresponding to different protonation states are compared with experiment. The simulations reveal that vibrational frequency distributions inside the fibrils are dominated by sidechain fluctuations. We further confirm earlier suggestions based on 2D-IR measurements that water molecules can be trapped inside the fibrils.